1983
DOI: 10.1128/iai.40.1.432-435.1983
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity and adherence of oral streptococci after repeated subculture in vitro

Abstract: Fresh isolates of Streptococcus mutans, Streptococcus sanguis, and Streptococcus salivarius from human dental plaque were all highly hydrophobic. After repeated subculture in vitro on blood agar, strains of S. mutans serotype c showed decreased hydrophobicity, whereas serotype dlg strains did not. Parallel to the decreased hydrophobicity in the serotype c strains, an impaired ability to adhere to hydroxyapatite was observed. A similar but less pronounced decrease in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(56 citation statements)
references
References 10 publications
4
51
1
Order By: Relevance
“…Various details which were originally employed in the paper describing the assay have since been modified and amended in various investigations. Parameters which have been altered include the suspending buffer [14,[17][18][19][20][21][22][23], the volumes and ratios of the phases employed [15][16][17][18][19][20][21]23,24], the test tubes used [15,19,20,23,24], duration of mixing [15,16,[18][19][20][21]23,24], and the test hydrocarbons employed [20]. Results obtained in this and other laboratories have shown that several aspects of the assay appear to be of major importance:…”
Section: Bath--methodological Aspectsmentioning
confidence: 99%
“…Various details which were originally employed in the paper describing the assay have since been modified and amended in various investigations. Parameters which have been altered include the suspending buffer [14,[17][18][19][20][21][22][23], the volumes and ratios of the phases employed [15][16][17][18][19][20][21]23,24], the test tubes used [15,19,20,23,24], duration of mixing [15,16,[18][19][20][21]23,24], and the test hydrocarbons employed [20]. Results obtained in this and other laboratories have shown that several aspects of the assay appear to be of major importance:…”
Section: Bath--methodological Aspectsmentioning
confidence: 99%
“…The influence of adsorbed salivary components on the surface hydrophobic properties of oral bacteria has not been previously reported though coating S. mutans cells with saliva reduces their affinity for hydroxyapatite (HA) [15]. Westergrun and co-workers [5] have shown that the hydrophobicity of S. mutans serotype c strains can be artificially reduced by repeated subculture on agar plates which correlated well with a reduction in the affinity of the cells for saliva-coated HA [7].…”
Section: Discussionmentioning
confidence: 98%
“…All bacteria were isolated from the oral cavities of monkeys (Macaca fascicularis) using previously described procedures [8][9][10] and had been subcultured no more than 4 times to minimize changes in their surface hydrophobic properties [7]. The methods used for the determination of the biochemical properties of the streptococci and their subsequent identification have been reported [8,11,12] except for the division of S. sanguis strains into 6 biotypes, which is shown in Table 1.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most oral streptococci [1] and a majority of the bacteria adhering to teeth [2] have hydrophobic surface properties. Recent publications also indicate that such properties are important for the adherence of both S. mutans [3] and Streptococcus sanguis [4,5].…”
Section: Introductionmentioning
confidence: 99%